Burnout among Canadian university faculty: applying a job demands-resources lens - Jason D. Edgerton; Jeff Biegun; Sandra Kouritzin; Satoru Nakagawa (Academia Mental Health & Well-Being)
There is growing research suggesting that the workload of university faculty members in Canada and elsewhere has intensified in recent years, with corresponding negative impacts on their mental and physical health, and their productivity. This study examines three hypotheses derived from the job demands-resources (JD-R) model—(1) job demands and burnout are positively associated; (2) job resources and burnout are negatively associated; (3) the association between job demands and burnout is moderated by job resources. Data were collected via online survey of faculty from 15 research intensive universities in Canada. Univariate, bivariate and OLS regression analyses of the data were conducted in SPSS, subsequent moderation analyses were then conducted within SPSS using PROCESS. The initial model supports the basic relationships between job demands, job resources and burnout as proposed by the JD-R model, but some of these associations diminish once interaction terms and control variables are added. No moderation effects were significant in the final model. The findings offer partial support for the JD-R model of burnout in a sample of university faculty and suggest that policies aimed at supporting professional autonomy and opportunity and work-life/family balance are important for reducing risk of burnout.